2010
DOI: 10.1002/eji.200939592
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes/macrophages and/or neutrophils are the target of IL‐10 in the LPS endotoxemia model

Abstract: IL-10 is a potent regulator of the innate and adaptive immune responses. Several cell types produce IL-10 and its receptor chains and these may regulate different immune responses. Here we report that inactivation of the IL-10 receptor (IL-10R1) gene in mice leads to an increased susceptibility to chemically induced colitis as in the classical IL-10-deficient mutant. To identify the cells regulated by IL-10 in immune responses, we generated several cell type specific IL-10R1-deficient mutants. We show that, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
110
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 25 publications
(27 reference statements)
10
110
1
Order By: Relevance
“…10 We recently demonstrated that IL-10 acting via the IL-10R on macrophages/ monocytes and/or neutrophils inhibits the proinflammatory immune response in the model of LPS endotoxemia. 33 In order to determine the influence of the intestinal flora in this model, we exposed germfree WT and IL-10 À/À mice to DSS. Surprisingly, both germfree WT as well as IL-10 À/À mice were even more susceptible to DSS-induced colitis than SPF IL-10 À/À mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…10 We recently demonstrated that IL-10 acting via the IL-10R on macrophages/ monocytes and/or neutrophils inhibits the proinflammatory immune response in the model of LPS endotoxemia. 33 In order to determine the influence of the intestinal flora in this model, we exposed germfree WT and IL-10 À/À mice to DSS. Surprisingly, both germfree WT as well as IL-10 À/À mice were even more susceptible to DSS-induced colitis than SPF IL-10 À/À mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma IL-10 was also elevated in patients with UPEC urosepsis (n = 57) compared with controls (n = 60) (B) (p = 0.001, unpaired Student t test, independent samples) illustrating IL-10 in the human immune response to UPEC. mechanism of immune regulation at the bladder-bacterial interface given the key role of IL-10R-dependent signaling in innate immunity (84). IL-10R is present on the surface of a variety of other human lymphoid and myeloid cells (85) and is upregulated during infection-induced inflammatory conditions such as sepsis (86).…”
Section: Discussionmentioning
confidence: 99%
“…3A), SAG21k induction of IL-10 was even more dramatic in Gli1 + colon stromal cells (Fig. 3E), and this induction was not observed in FACS-isolated hematopoietic or epithelial cell populations from the colons of DSSexposed animals ( The antiinflammatory role of the IL-10 cytokine in IBD has long been known, with inactivating mutations in IL-10 or its receptor causally linked to IBD in humans and mice (1,2,(19)(20)(21). To determine whether IL-10 expression indeed mediates the protective effect of Hh stromal response, we exposed IL-10 mutant mice (IL-10 −/− ) to DSS and treated with SAG21k.…”
Section: Reduction Of Hh Pathway Activity Exacerbates Acute Dss-inducedmentioning
confidence: 96%